2011
DOI: 10.1016/j.ydbio.2011.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cis regulatory features in the embryonic zebrafish genome through large-scale profiling of H3K4me1 and H3K4me3 binding sites

Abstract: An organism’s genome sequence serves as a blueprint for the proteins and regulatory RNAs essential for cellular function. The genome also harbors cis-acting non-coding sequences that control gene expression and are essential to coordinate regulatory programs during embryonic development. However, the genome sequence is largely identical between cell types within a multi-cellular organism indicating that factors such as DNA accessibility and chromatin structure play a crucial role in governing cell-specific gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 65 publications
2
71
0
Order By: Relevance
“…Data mining of a genome-wide study of histone modification marks found in 24hpf zebrafish embryos revealed a sequence marked by H3K4me3 overlapping with the transcriptional start site of zebrafish lama1 [42], consistent with the known association of H3K4me3 histone modifications with promoter elements and the presence of the lama1…”
Section: Gli/zic Binding Sites Within the Lama1 Intronic Enhancer Forsupporting
confidence: 69%
See 1 more Smart Citation
“…Data mining of a genome-wide study of histone modification marks found in 24hpf zebrafish embryos revealed a sequence marked by H3K4me3 overlapping with the transcriptional start site of zebrafish lama1 [42], consistent with the known association of H3K4me3 histone modifications with promoter elements and the presence of the lama1…”
Section: Gli/zic Binding Sites Within the Lama1 Intronic Enhancer Forsupporting
confidence: 69%
“…Histone methylation marks were extracted from the ChIPSeq data performed by Aday et al on 24hpf zebrafish embryos, mapped on the zebrafish genome (zv7) and uploaded on the UCSD genome browser server [42].…”
Section: In Silico Analysesmentioning
confidence: 99%
“…2012). TSSs marked with H3K4me3, a modification associated with transcriptionally active promoters (Aday et al 2011), were significantly earlier replicating than TSSs lacking H3K4me3 (Fig. 3C).…”
Section: Characteristics Of the Zebrafish Replication Timing Programmentioning
confidence: 95%
“…Histone marks and chromatin remodeling complexes modify chromatin conformation, regulating the accessibility of transcription factors to cis-regulatory regions. Some epigenetic marks have been associated with specific groups of regulatory elements; in humans (Heintzman et al, 2009), zebrafish (Aday et al, 2011), and flies (Negre et al, 2011) the mono-methylation of histone H3 lysine 4 (H3K4me1) is usually found in active enhancer regions, close to areas of open chromatin. A recent study showed that the activity of the protein LSD1 (a demethylase of H3K4 and H3K9) is essential for differentiation of mouse embryonic stem cells (Whyte et al, 2012).…”
Section: The Unknown Spatial Distribution Of Cis-regulatory Informationmentioning
confidence: 99%